The Network Map of the Fields of Interest in Information Sciences in Croatia / Jadranka Lasić-Lazić, Đilda Pečarić, Nikolaj Lazić - Lasić-Lazić, Jadranka (Array, 2013)
The research of topics in which scientist were interested as well as classification of the field of information and communication sciences in the last ten years has undergone major changes. In this research we were focused on Croatian scientists. The dispute, which is now growing over the question what belongs to the field, led us to investigate which problems and which topics are pursued by researchers in information and communication sciences. It is clear that scientific filed should not be seen in the narrow framework of the state, but it is also clear that the national strategy for the development of science and investing in research projects are also important for the development of a particular field. The method used to research the development of information and communication science was a content analysis of papers written by scientists who published in the field of information and communication sciences from year 2009 to 2012. The results obtained in this analysis were compared with the results of the analysis for the period from year 1991 to 2009. The purpose of this paper is to show the extensiveness of topics that are part of the field, to connect the concepts of traditional topics of particular disciplines of science with information and communication technological concepts that are increasingly open entrance of information sciences to other scientific fields.